Peningkatan Kinerja Pemasaran Melalui Disruptive Innovation Yang Berbasis Intellectual Capital pada UMKM kabupaten Sukamara, Kalimantan Tengah - Sindania Sindania; Sri Hartono (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2020)
This study aims to analyze whether there is an effect of human capital, structural capital and relational capital on marketing performance and disruptive innovation as an intervening variable in culinary MSMEs in Sukamara district, Central Kalimantan. The sampling technique uses a non-probability sampling technique using purposive sampling method, where the sample is selected by certain criteria. The sample in this study was taken as many as 60 respondents with a research instrument in the form of a questionnaire that has been tested for validity and reliability. The data analysis technique used to answer the hypothesis of multiple regression analysis with the SPSS 22 data processing program shows that human capital has no effect on marketing performance, structural capital has a negative and insignificant effect on marketing performance and relational capital has a positive and significant effect on marketing performance. Researchers also found that the disruptive innovation variable was able to mediate the independent variable on marketing performance.